Pre-operative immunomodulatory nutrition and post-operative outcomes of surgical treatment of gastrointestinal surgery: a systematic review - Almottowa, Hisham Abdullah; Al-Khars, Ahmed Salman; Kurdi, Maan Almotaz; Almusawi, Ahmed Kamal; Hakeem, Amr Rashad; Almashat, Nada Ahmad; Jowharji, Abdulaziz Wajdi; Aljaza, Turki Salem; Bukhary, Mohammad Ismail; Almahmudi, Hussain Oamr; Alsaeidi, Mased Ali (International Journal Of Community Medicine And Public Health, 2021)
Malnutrition is a major health problem in cancer evident in up to 80% of patients. It was associated with high mortality and morbidity, especially with surgical treatment of cancer. That is why many studies are investigating efficient treatment for this problem. One of these treatments is immunomodulatory nutrition. Immunomodulatory nutrition has shown efficacy towards malnutrition, immune status, and other comorbidities. However, there is still a debate about whether it is efficient or not. Five databases were searched using specific search terms. We only included randomized controlled trials that studied the efficacy of preoperative immunomodulatory nutrition before surgical treatment of gastrointestinal carcinoma. The studies were assessed for the quality of evidence. Twenty-three studies were included for the systematic review. Most studies had a low risk of bias. We assessed the efficacy of immunomodulatory nutrition regarding immune markers, infectious complications, non-infectious complications, biological markers, the length of stay, and mortality. Immunomodulatory nutrition has significantly enhanced immune status, biological markers, and post-operative complications. However, it does not have a significant improvement in the mortality rate or hospitalization duration. The immunomodulatory nutrition has promising results in enhancing immune status, and biological markers. However, its effect on post-operative infectious and non-infectious complications is still under debate. Immunomodulatory nutrition had no effect on mortality rates among cancer patients.